Investigation of the anti-hyperglycemic and antioxidant effects of wheat bread supplemented with onion peel extract and onion powder in diabetic rats - Masood, Sara; Rehman, Attiq ur; Bashir, Shahid; El Shazly, Mohamed; Imran, Muhammad; Khalil, Palwasha; Ifthikar, Faiza; Jaffar, Hafiza Madiha; Khursheed, Tara (Springer Nature, 2021)
Aim: Onion is one of the commonly cultivated and consumed vegetables rich in nutrients and phytochemicals. Various nutraceuticals are found in the outer fleshy layers and dry peel of onion which usually is treated as a common biowaste. Diabetes mellitus is a leading non communicable disease causing hyperglycemia and increased production of free radicals that potentially disrupts antioxidant enzymatic activity. Considering global consumption of wheat, the present study was designed to evaluate the anti-hyperglycemic and antioxidant effects of wheat bread supplemented with onion peel extract (OPE) or onion powder (OP) on diabetic rats. Methods: In this study, ethanolic extract of onion peel and onion bulb were prepared separately. Male Sprague Dawley rats were divided into 6 groups (n = 7). Different regimens of supplemented wheat bread (OPE (1% and 3%) and OP (5% and 7%)) were given to diabetic rats for eight weeks, plain bread was used as the control. Blood glucose level, body weight and activities of SOD, CAT, GPx, GR, GSH and MDA in the liver and kidney tissues were evaluated. Statistical analysis was performed using SPSS Version (25) and Dunnett’s multiple comparison test. Results: Bread supplementedwith 1%and 3% onion peel extract and 7%onion powder significantly reduced blood glucose levels and MDA in the treated rats compared with the control group diabetic rats. Body weight of diabetic rats was reduced for control group, while onion supplemented diet improved the body weight of treated rats. Onion supplementation also brought significant improvement in antioxidant enzyme activities among the treated diabetic rats. Conclusion: These findings suggested that onion supplementation is effective in lowering blood glucose and could potentially aid in protecting organs from oxidative stress.
Keywords: Onion powder; Onion peel extract; Antioxidant activity; Hypoglycemic activity; Wheat bread; Phytochemicals